Breastfeeding: study of prevalence and determinant factors in the first six months of life - Oliveira, Mário (2016)
Introduction: Breastfeeding is unequivocally the best way of feeding the baby and the best that the mother can offer to in the first months of life. However, in Portugal, despite the fact that breastfeeding rates are high at the time of discharge from maternity, these fall quickly. Objectives: Evaluate the prevalence of breastfeeding in the first six months of age; identify the factors that influence its abandonment and assess the relationship between the duration of breastfeeding and the age and educational level of the mother. Methodology: Observational, analytical and cross-sectional study of a convenience sample (n=83) obtained through a questionnaire applied to mothers of children enrolled in UCSP Vagos 1, who resorted to the unit for child health consultation of the six months between July 2013 and June 2014. Results: Of the mothers studied (average age 29,4 ± 4,8 years), 71% were married, 59% primiparous and 34,6% had 12th year of schooling. The regular surveillance of the pregnancy occurred in all pregnant women (100%), highlighting those performed by the family doctor (49,5%) and the average weight at birth was 3251 ± 724g. At the time of discharge from maternity 75% were breastfeeding the child exclusively, this percentage decreased to 57,7% at three months and 46,1% at six months. The biggest cause reported for the abandonment was poor weight progression (42,9%). Conclusion: The rate of breastfeeding at maternity discharge(75%) is below the majority of studies found and made in Portugal, with a gradual but slow decrease in the first six months. However, the rates presented are below the international recommendations and the national goal. These results draw attention to the lack of or inadequate strategies related to the health services involved in the process. The youngest and less educated mothers are the priority target of activities of breastfeeding promotion.